Performance analysis and improvement of a typical telephone response system of VA hospitals: A discrete event simulation study - Shi, Jing; Erdem, Ergin; Peng, Yidong; Woodbridge, Peter; Masek, Christopher (International journal of operations & production management, 2015)
Purpose - Telephone response system is the frontline of hospital operations. The purpose of this paper is to analyze a representative telephone response system of Veterans Affairs (VA) hospitals, address the existing inefficiency issues such as long call waiting time, and improve system resilience to changes. Design/methodology/approach - Resource sharing schemes are proposed to improve the system performance in answering calls related to appointment booking and medication renewal. Discrete event simulation is adopted to model the current system and the resource sharing schemes. Findings - The resource sharing schemes dramatically improve system performance reflected by the decrease of call waiting time and queue, as well as the extreme high utilization of agents in a key unit. Compared with the less desired alternative of hiring additional employees to mitigate the performance issues, the resource sharing schemes perform at par or even better. Sharing more resource during the peak hours can further balance the agent workload. Practical implications - The resource sharing schemes could alleviate staffing shortage, long waiting time, and high-abandonment rate in the bottle-beck unit of the system, and lead to better utilization of scarce resources on the hospital floor. The concept reflects localized centralization efforts in traditionally highly decentralized telephone operations in hospital systems. Originality/value - This research provides a structured approach to analyze the operations of a VA telephone response system. The developed simulation model is validated, and this provides a valuable tool for management to analyze the complicated telephone operations of the telephone systems of other VA and non-VA hospitals. Resource sharing constitutes a cost-effective solution for improving system performance and resilience.